PENERAPAN METODE OUTDOOR STUDY UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV PADA MATA PELAJARAN IPS DI SD NEGERI 2 KARANG ENDAH - Marindes, Wahyu; Jumroh; Melinda Puspita Sari Jaya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of implementing the Outdoor Study learning method to improve student learning outcomes in social studies subjects of grade IV of SD Negeri 2 Karang Endah. This study is an experimental study in the form of Pre Experimental Design with One Group Pretest Posttest Design. The population in this study was all grade IV of SD Negeri 2 Karang Endah. The determination of the sample used a sample survey technique, so that there were groups from one class, namely Class IV. The results of this study were obtained from grade IV students of SD Negeri 2 Karang Endah with a sample size of 14 students. The instruments in the study were in the form of observation, tests and documentation. Based on the results of the research and discussion, it was obtained that t_count = 6.388 and t_table = 2.160 means t_count > t_table, so it can be concluded that there is an increase in the learning outcomes of grade IV students in social studies after the Outdoor Study method was implemented at SD Negeri 2 Karang Endah. From the results of the study, it can be said that the learning outcomes of students before and after using the outdoor study learning method there is an increase in student learning outcomes. Thus, there is a quite effective difference between the social studies learning outcomes of grade IV students and normal learning.